Cytotoxic Assay From Stem Bark Aglaia minahassae and Aglaia simplicifolia Against HeLa Cervical Cancer Cell Lines - Nunung Kurniasih; Hersa Milawati; Mohamad Fajar; Rizky Abdulah; Desi Harneti Putri Huspa; Unang Supratman (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Cervical cancer ranks as the 2nd leading cause of female cancer in Indonesia. One of healing methods is chemotherapy, but this method still has many side e ects and also expensive treatment. Therefore, natural products discoveries need to be developed due to its important role as an alternative for anti- cancer drug. The aim of this research was to get IC50 value from methanol, n-hexane, ethyl acetate, and n-buthanol from stem bark of A. minahassae dan A. simplicifolia. Stem bark of A. minahassae (1.6 kg) and A. simplicifolia (1.1 kg) was grounded by methanol and its extract is successively extracted by n-hexane, ethyl acetate, and n-buthanol. Their extract’s cytotoxicity was then evaluated against HeLa cell lines. This research showed that A. minahassae’s most cytotoxic extract against HeLa cell lines was n-hexane (IC50 = 27.4190 μg/mL) and n-buthanol (IC50 = 4.3924 μg/mL). Meanwhile, A. sim- plicifolia most cytotoxic extract extract against HeLa cell lines was n-hexane (IC50 = 23.3098 μg/mL). Key words: A. minahassae, A. simplicifolia, cytotoxic assay, HeLa cell lines